Birkeland current boundary flows. Issue 4 (19th April 2017) - Archer, W. E.; Knudsen, D. J.; Burchill, J. K.; Jackel, B.; Donovan, E.; Connors, M.; Juusola, L.
Abstract: Intense zonal ion velocity jets in the northern nightside auroral zone are measured during quiet geomagnetic conditions by the Swarm satellites around 500 km altitude. These velocity jets, exceeding 1 km/s in over 50% of orbits measured, range from 20 to 100 km in meridional thickness and reach a maximum at the boundary between upward and downward field‐aligned current. On average they represent a potential difference of approximately 3 kV between the R1/R2 currents. This boundary also separates different regions of electron temperature and meridional flow and is associated with ion upflows and anisotropic heating. Both dawnward and duskward velocity jets are observed, including some oppositely directed pairs bounding regions of upward field‐aligned current. Coincident ground‐based observations place ion velocity jets adjacent to auroral arcs, embedded in the auroral electrojets. Previous literature has focused on fast flows occurring in regions of relative low conductivity surrounding auroral arcs, typically during geomagnetically active conditions, and does not address the occurrence frequency of these events. We show ion velocity jets to be a persistent and ubiquitous property of the electrodynamics of quiet time R1/R2 current closure near midnight in the winter hemisphere. Plain Language Summary: Narrow regions of fast flowing ions are observed by the Swarm satellites near midnight in the auroral zone of the winter hemisphere. These flows are distinct from similar phenomena studied previously in that they occur during geomagnetically quiet periods, are narrow in latitude (between 20 and 100 km wide), and clearly mark the boundary between upward and downward magnetic field‐aligned currents. We also show them to be associated with heating and upward flow of ionospheric ions. Key Points: Intense, latitudinally narrow zonal ion flows are regularly observed by the Swarm satellites in the nightside auroral zone The morphology of these flows with MLT is consistent with Pedersen currents closing Region 1 and Region 2 Birkeland currents These flows are associated with ion upflow, anisotropic heating, and mark a transition in FAC, meridional flow, and electron temperature